2001
DOI: 10.1590/s0034-89102001000300006
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of bacterial meningitis among children in Brazil, 1997-1998

Abstract: ObjectiveTo document the incidence and the descriptive epidemiology of bacterial meningitis among individuals under age 20 in a geographically defined region in Brazil during the two-year period immediately preceding the introduction of Haemophilus influenzae type b (Hib) vaccines into the national immunization program of Brazil. Methods Population-based epidemiological study of all cases of bacterial meningitis reported among residents of Campinas, Brazil, under age 20 (n=316,570) during the period of 1997-98… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
9
0
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 15 publications
5
9
0
7
Order By: Relevance
“…Considering the absolute frequency of the cases, the highest ratio was observed in males of the 1-4-years age group in MG, which agrees with the findings of other studies [24][25][26] . Possible explanations for the high proportion of male cases are the facts that men have a tendency of taking less care of their health, expose themselves to a higher amount of risky situations, and seek the help of health care services less often than women.…”
Section: Ethical Considerationssupporting
confidence: 92%
See 1 more Smart Citation
“…Considering the absolute frequency of the cases, the highest ratio was observed in males of the 1-4-years age group in MG, which agrees with the findings of other studies [24][25][26] . Possible explanations for the high proportion of male cases are the facts that men have a tendency of taking less care of their health, expose themselves to a higher amount of risky situations, and seek the help of health care services less often than women.…”
Section: Ethical Considerationssupporting
confidence: 92%
“…The elevated percentage of cases with non-specified etiology reflects problems in the care process, i.e., in collecting, transporting, and/ or processing of cerebrospinal fluid samples, which corroborates the findings of other studies 25,32 .…”
Section: Ethical Considerationssupporting
confidence: 88%
“…The mortality rate was 11.1% (Table 2), and N. meningitidis type B was the cause of all of the deaths. The high rate of failure to determine the etiological agent at GTH is consistent with other Brazilian reports, which range from 46.8 to 55.5% 3,6 . Although only 6.5% of the patients in the current study reported previous use of antibiotics, which is most likely an underestimation, the low bacterial culture rate is probably greatly affected by the previous use of antibiotics 5 .…”
supporting
confidence: 90%
“…The risk of Hib meningitis found for the pre-vaccine period was similar to that observed in Campinas, southeastern Brazil (17x10 5 ), and is comparable to those found in European countries such as Austria, Spain, and England. 9,14 The impact of the Hib vaccination has also been evaluated in other Brazilian regions. In Curitiba, southern Brazil, the incidence of meningitis dropped from 35.5 to 9.7x10 5 (72% reduction), one year after the introduction of the vaccine.…”
Section: Discussionmentioning
confidence: 99%